Dysphagia in schizophrenia: pathological mechanisms and treatment recommendations - Wang, Jiahui; Gao, Caifeng; Fu, Cuiyuan; Li, Kun (Frontiers in Psychiatry, 2024)
Schizophrenia is a chronic, severe, and disabling mental disorder that significantly impacts individuals' lives. Long-term treatment with antipsychotic drugs, coupled with the complications of the disease itself, increases the risk of dysphagia in patients. These disorders further heighten the likelihood of choking and asphyxia death among this population. This project aims to comprehensively review the pathological mechanisms behind dysphagia in schizophrenia, alongside proposing early screening and evaluation methods. It also suggests treatment recommendations to mitigate the risks and complications associated with dysphagia in these patients.